Hypothetical Learning Trajectory (HLT) terhadap Kemampuan Literasi Numerasi pada Materi Lingkaran - Muhammad Haris Hajriyanto; Mega Nur Prabawati; Nani Ratnaningsih (Cipta Media Harmoni, 2024)
This study is being conducted to identify the learning disabilities in math literacy at SMPN 3 Kalipucang kelas VIII during the second semester of the 2023–2024 school year. The method that is used is a qualitative approach called Didactical Design Research. Study focus is on three study subjects: students with weak mathematical skills (S1), students with strong mathematical skills (S2), and students with weak mathematical skills (S3). The results of the study indicate that students in S1 experience difficulties learning epistemological obstacles, students in S2 experience difficulties learning both didactic and epistemological obstacles, and students in S3 experience difficulties learning ontogenic, didactic, and epistemological obstacles. In order to overcome this obstacle, researchers have developed learning materials that are oriented toward numerical literacy with the goal of raising student achievement standards Researchers used Learning Obstacle Identification as a basis to create a Hypothetical Learning Trajectory (HLT) that focuses on literacy numeration of material circles.